Radiation-induced crosslinking of acetylene-impregnated polyesters. II. Effects of preirradiation crystallinity, molecular structure, and postirradiation crosslinking on mechanical properties - W. Punyodom (2018)
Electron beam-irradiated crosslinking has been studied in a series of acetylene-impregnated polyesters and amorphous copolyesters, including poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT), poly(cyclohexane dimethylene terephthalate) (PCDT), and poly(cyclohexane dimethylene terephthalate-co-ethylene terephthalate) (P(CDT-co-ET)) having 29 and 60 wt % ethylene terephthalate (ET). The extent of crosslinking was observed by gel fraction measurements and was found to be significantly influenced by the aliphatic chain content of the polyesters (PET < PBT < PCDT). In addition, as the preirradiation crystallinity of the polyesters was reduced, the extent of acetylene-enhanced crosslinking was greatly raised. Decreases in the postirradiation crystalline melting temperature and degree of crystallinity were observed in all the polyesters, using differential scanning calorimetry measurements. Particularly significant findings have been the shift in the glass-transition temperatures (Tg) to higher temperatures and the decrease in loss tangents at higher temperatures, both of which confirm that crosslinking has taken place. The storage moduli (E′) in the rubbery plateau region of PCDT and P(CDT-co-ET) were significantly affected by irradiation dose. Increased network tightness in postirradiated PBT and PCDT films was also inferred from melt-rheology measurements, in which stress relaxed more slowly following a stepped strain. Improvements in the mechanical properties of the irradiated polyesters and co-polyesters were clearly evidenced by the increased modulus at higher temperatures, observed using dynamic mechanical thermal analysis and melt-rheology methods. © 2006 Wiley Periodicals, Inc.